Dampak Negatif Game Online Free Fire Terhadap Keterampilan Bahasa Anak Usia 4 Tahun - Ina Rotu Duja, Azka; Lidia Fitri, Siska; Nursepta Salsabila, Yulaika; Ichsan Nurjam’an, Muhammad (Program Studi Pendidikan Bahasa dan Sastra Indonesia, Fakultas Keguruan dan Ilmu Pendidikan, Universitas Islam Makassar, 2026)
The uncontrolled use of digital games among early childhood may affect children’s language and emotional development. This study aims to describe the impact of digital game addiction on the language skills and emotional development of a four-year-old child. The research employed a qualitative descriptive approach with a single research subject, a four-year-old child suspected of experiencing addiction to the digital game Free Fire. Data were collected through direct observation and field notes focusing on the child’s language behavior and emotional responses during interactions with the surrounding environment. The findings indicate that intensive exposure to digital games influences the child’s language use, as reflected in the tendency to imitate vocabulary and expressions of game characters that are not appropriate for the child’s developmental stage. In addition, the child showed a decline in contextual language ability and reduced social interaction with others. From an emotional perspective, the child demonstrated emotional instability, such as excessive anger when prohibited from playing the game and difficulties in self-regulation. The main contributing factors include limited parental supervision and assistance, as well as excessive gaming duration. The negative impacts identified encompass three developmental aspects: language skills, socio-emotional development, and cognitive development related to attention and concentration. This study highlights the importance of collaboration between parents and the surrounding environment in regulating children’s digital device use through limiting gaming duration, providing alternative educational activities, and promoting early digital literacy so that technology can support children’s balanced and optimal development.